Analysis of Direct and Flanking Sound Transmission Between Rooms with Curtain Wall Facades. (November 2015) - Martello, N. Zuccherini; Secchi, S.; Fausti, P.; Cellai, G.; Santoni, A.
Abstract: Curtain walls have nowadays reached good performance in terms of façade sound insulation, thermal insulation and solar protection. In this work, flanking and direct structural transmission are analysed with reference to the joints of the mullion of the curtain wall with lightweight plasterboard partitions. Airborne sound insulation and vibrational measurements were made in two adjacent rooms affected by the acoustic problems determined by the curtain wall joint. Traditional acoustic measurements carried out according to EN ISO 16283-1 highlight problems in sound insulation between rooms, but without any indication on different sound transmission paths through the wall. Vibrational measurements were made for every part of the system (frame columns and beams, windows' glasses, plasterboard wall, plasterboard false ceiling, etc.) to better understand the sound transmission paths in these kinds of structures. Taking into account previous works and measurements made in this research field, different solutions for curtain wall structures are analysed and technical suggestions are given to improve airborne sound insulation between rooms separated by partitions mounted up to metal frames.